2010
DOI: 10.4025/actasciagron.v32i4.2502
|View full text |Cite
|
Sign up to set email alerts
|

Influência de pontas de pulverização e adjuvante no controle químico da ferrugem asiática da soja

Abstract: RESUMO.Este trabalho teve como objetivo otimizar o controle químico da ferrugem asiática da soja, avaliando a deposição de fungicida no dossel da cultura ao utilizar diferentes pontas de pulverização, em dois volumes de calda, com e sem a adição de adjuvante à calda. O ensaio foi conduzido no delineamento em blocos casualizado, com quatro repetições, em esquema fatorial (3 x 2 x 2): três tipos de ponta de pulverização (jato plano defletor, jato plano duplo e jato plano duplo com indução de ar), dois volumes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
1
8
0
5
Order By: Relevance
“…A associação de fungicidas e adjuvantes foi testada na cultura da soja (CUNHA & PERES, 2010;AGUIAR-JÚNIOR et al, 2011) e milho (JADOSKI et al, 2009;WOLF et al, 2009); entretanto, os autores não encontraram trabalhos relacionados à cultura do trigo. O objetivo deste trabalho foi verifi car se a adição de adjuvantes à calda com fungicidas favorece o controle químico das doenças foliares e da espiga da cultura do trigo.…”
Section: As Doenças Foliares E Da Espiga Podem Reduzir Acentuadamenteunclassified
“…A associação de fungicidas e adjuvantes foi testada na cultura da soja (CUNHA & PERES, 2010;AGUIAR-JÚNIOR et al, 2011) e milho (JADOSKI et al, 2009;WOLF et al, 2009); entretanto, os autores não encontraram trabalhos relacionados à cultura do trigo. O objetivo deste trabalho foi verifi car se a adição de adjuvantes à calda com fungicidas favorece o controle químico das doenças foliares e da espiga da cultura do trigo.…”
Section: As Doenças Foliares E Da Espiga Podem Reduzir Acentuadamenteunclassified
“…Butler-Ellis (2000) argue that the droplets formed by the tips with air induction technology are more sensitive to changes in the physical properties of the spray when forming the droplets, which is precisely what occurs when the adjuvant is added. In a similar study, Cunha and Peres (2010) observed no increase in the deposition in the lower stratum. The effects of adjuvants vary greatly according to each application situation.…”
Section: Resultsmentioning
confidence: 61%
“…Antuniassi et al (2004) found that the worst deposition results in the lower stratum of soybean plants were obtained using air induction tips. Cunha and Peres (2010) found no difference in droplet deposition in the upper and middle canopy strata, whether they used a deflector tip, a twin flat tip or a twin flat tip with air induction, which produce medium-thick, fine-medium, and very thick droplets, respectively, showing that an air induction tip can often have the same deposition performance obtained by a tip that produces finemedium droplets. All these authors used 200 and 250 L ha -1 of application rate, while the current trend is to reduce this rate to levels such as the 120 L ha -1 applied in the present study.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, BUTLER ELLIS et al (2004) reported higher retention of spray solution on wheat leaves with a reduced surface tension and attributed this phenomenon to a decrease in the size of sprayed droplets, which is allied with a reduced impact when droplets hit the leaves. CUNHA et al (2010) verified that adjuvants do not change the deposition of droplets on soybean plants but reduce the incidence of Asian soybean rust. This effect depends on the type of spraying nozzle used.…”
Section: Resultsmentioning
confidence: 93%